2018
DOI: 10.1002/cem.3036
|View full text |Cite
|
Sign up to set email alerts
|

Elemental fingerprint profiling with multivariate data analysis to classify organic chocolate samples

Abstract: Chocolate is an appreciated food derived from cacao fruit. The flavonoids and minerals present in the chocolate have benefits to health, and some specific minerals are known to be toxic. Because of differences in their production systems, organic chocolate has a distinguishable pattern in mineral concentrations than conventional chocolate. Aiming for authenticity and study of the toxic elements in organic chocolate, we present in this work a simple method to classify organic chocolate samples based on elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The largest difference was observed in the Fe content that was twice as high in conventional chocolates as in organic samples. The elemental composition of 36 chocolate samples characterised by ICP-MS, including 38 elements, has been previously used to classify organic chocolate by Junior et al ( Junior et al, 2018 ), who found higher concentrations of Fe, Zn and Mg in the conventional than in the organic chocolate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The largest difference was observed in the Fe content that was twice as high in conventional chocolates as in organic samples. The elemental composition of 36 chocolate samples characterised by ICP-MS, including 38 elements, has been previously used to classify organic chocolate by Junior et al ( Junior et al, 2018 ), who found higher concentrations of Fe, Zn and Mg in the conventional than in the organic chocolate.…”
Section: Resultsmentioning
confidence: 99%
“…The approaches used so far for authentication purposes can be divided in targeted and untargeted analysis. Targeted analysis addresses the determination of specific substances in food and are mostly represented by analysis of stable isotopes by Isotope Ratio Mass Spectrometry (IRMS) ( Liu et al, 2020 ), by multi-elemental analysis frequently carried out with ICP-based methods ( Junior et al, 2018 ) and by chromatographic methods for the determination of metabolites ( Eibler et al, 2018 ), or by combination of several of them. Untargeted analysis aims at analysing, in a holistic approach, all substances, some known and some unknown, in a certain sample.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…chocolate. Junior et al (2018) used DA based on elemental composition to differentiate between organic and conventional chocolates and Bertoldi et al (2016) used 13 chocolates as a validation set to test the efficiency of their DA model for the classification of cacao beans by geographical origin.…”
mentioning
confidence: 99%